Modernización de regadíos con aguas subterráneas en ámbitos semiáridos - Gómez Espín, José Mª; García Marín, Ramón; Gil Meseguer, Encarnación (M+A. Revista Electrónica de Medioambiente, 2007)
Nearly 3,5 million hectares are irrigated in Spain, which involves the use of more than 80% of the available water supply. More than one million hectares are irrigated using water that comes from the collection and exploitation of deep aquifers. Thus, farmers’ standards of living and water availability will be significantly improved by the implementation of improvement and modernization policies, with the aim of reducing water needs and increasing exploitation efficiency. In this study, we present some of the modernization programmes that have been applied to an over-exploited aquifer (Ascoy-Sopalmo) in the region of Murcia. More than 54 Hm3 are extracted from it for the irrigation of 10.000 hectares in the municipal areas of Cieza, Jumilla, Abarán, Blanca, Ulea, Molina de Segura, Archena, Abanilla and Fortuna, among others.
Keywords: Subterranean Water; Irrigation Modernization; Ascoy-Sopalmo Aquifer; Region of Murcia